(3JShjb GdNOeGJs - (3Ydj Jhajb CMeO(B, (3GdMGLs; (3SejQ MSjf eMehO(B, s ((3YeGf(B:s (3OGQ GdGYUGQ(B,s, 2011)
(3ebOeI aj GdJQhjL GdJLGQj , GdJQhjL cYedjI EJUGd , Gdeaghe GdMOjK dEOGQI GdJShjb ,GdeRjL GdJShjbj ddNOeGJ , GdJObjb GdJShjbj , GdJShjb GdaYGd , GdJShjb gh LhOI GdMjGI , GSJQGJjLjI GdJQhjL , GdJShjb GdRQGYj (B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJQhjL GdJLGQIs; (3GdJShjbs; (3GdNOeGJs; (3GdNOeGJ `` JShjbs